An unusual arrangement of the neurovascular structures in one ethmoidal foramen of the human orbit - K.S. Mpolokeng; G.J. Louw (Elsevier, 2020)
The anatomical landmarks of the medial orbital wall are vital for orbital surgeries. Understanding of the medial orbital wall, the number, morphology and location of ethmoidal foramina, is important in order to help reduce intraoperative risks. It is also important for proper identification of all anatomical structures during sinus surgery. The reported incidence rate of both minor and major orbital surgical complications varies between 0.5 and 30%. The aim of this study is to report the morphology of a rare variation of the ethmoidal foramen present in the left orbit of one body. Both orbits were studied of which one revealed a rare variation. The eyeballs were exenterated from the orbits with part of the optic nerve, leaving the vascular supply and extraocular muscles intact. A further dissection was performed in both orbits to remove excess orbital tissue for a proper visualisation of the orbital blood supply and their points of exit. Digital photographs were taken and stored on a computer. The arterial system was traced on a computer using Microsoft PowerPoint tools to highlight their route on the medial orbital. Ethical approval was granted for the main study with reference: 469/2018. The medial orbital wall of the left orbit was concluded to have a single ethmoidal foramen. Two blood vessels were identified emerging from this single foramen and one blood vessel entering in an unusual way. The right orbit did not show a similar observation. Few previous studies found a single foramen in orbits, however, there was only one blood vessel that was seen passing through the foramen. Knowledge of the medial orbital wall foramina may serve as a guide to clinicians while treating haemorrhages of ethmoidal vessels and anterior ethmoidal nerve syndrome. In addition, this knowledge will help reduce intraoperative risks and injury to the neurovascular bundle. Further research will be conducted to investigate the frequency of this variation in a South African context. Keywords: Orbits, Ethmoidal foramen, Ethmoidal artery, Neurovascular, Orbital wall